Body Dysmorphic Disorder and the influence of the media in demand for plastic surgery: the importance of proper evaluation - Alexandre Kataoka; Renato Rocha Lage; Camila Cristina Silva Mendes; Nikole guimarães Soares (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Since the beginning, plastic surgery has improved self-esteem and acceptance in a society that idealizes the cult of the body. The pressure of consumption and the ease of undergoing plastic surgery becomes an obsession in these patients’ lives. Method: Female patients who underwent psychological evaluation and follow-up throughout the surgical and plastic surgery procedure, aged between 19 and 57, answered the Sociocultural Attitudes Questionnaire concerning appearance and the Body Dysmorphophobia Symptom Scale. Results: Of the 38 patients evaluated, 17 have the media as an influence concerning their body image and have symptoms of Body Dysmorphic Disorder (BDD), 13 patients have the media as an influence on their body image, but they do not have BDD symptoms, and in eight patients the media does not influence their body image, and they do not have BDD symptoms. Conclusion: The importance of a multidisciplinary team, with a psychologist, is highlighted to evaluate and monitor the patient throughout the surgical process, as the early diagnosis of BDD will avoid dissatisfaction with the result of the plastic surgery and, mainly, future court lawsuits.